Influence of Growth Phase, pH, and Temperature on the Abundance and Composition of Tetraether Lipids in the Thermoacidophile Picrophilus torridus - Feyhl-Buska, Jayme; Chen, Yufei; Jia, Chengling; Wang, Jin-Xiang; Zhang, Chuanlun L.; Boyd, Eric S. (Frontiers in Microbiology, 2016)
The abundance and composition of glycerol dibiphytanyl glycerol tetraether (GDGT) and glycerol tribiphytanyl glycerol tetraether (GTGT) lipids were determined as a function of growth phase as a proxy for nutrient availability, the pH of growth medium, and incubation temperature in cultures of the thermoacidophile Picrophilus torridus. Regardless of the cultivation condition, the abundance of GDGTs and GTGTs was greater in the polar than core fraction, with a marked decrease in core GDGTs in cultures harvested during log phase growth. These data are consistent with previous suggestions indicating that core GDGTs are re-functionalized during polar lipid synthesis. Under all conditions examined, polar lipids were enriched in a GDGT with 2 cyclopentyl rings (GDGT-2), indicating GDGT-2 is the preferred lipid in this taxon. However, lag or stationary phase grown cells or cells subjected to pH or thermal stress were enriched in GDGTs with 4, 5, or 6 rings and depleted in GDGTs with 1, 2, 3, rings relative to log phase cells grown under optimal conditions. Variation in the composition of polar GDGT lipids in cells harvested during various growth phases tended to be greater than in cells cultivated over a pH range of 0.3 to 1.1 and a temperature range of 53°C to 63°C. These results suggest that the growth phase, the pH of growth medium, and incubation temperature are all important factors that shape the composition of tetraether lipids in Picrophilus. The similarity in enrichment of GDGTs with more rings in cultures undergoing nutrient, pH, and thermal stress points to GDGT cyclization as a generalized physiological response to stress in this taxon.